Understanding the influence tenure has on meanings of home and homemaking practices. Issue 1 (20th November 2017) - Bate, Bronwyn
Abstract: Within Anglophone societies, the concept of home is closely tied to homeownership, and consequently, importance is placed on owner‐occupied tenure in the meaning and making of home. However, understanding home in this way is problematic because it excludes the significant proportion of people who rent both publicly and privately. This article provides an overview of the small amount of literature that examines the impact tenure has on the meaning and making of home within Anglophone societies, in particular, Australia, the United States, and the United Kingdom. Two key arguments are made. Firstly, tenure laws and policies make an important contribution in shaping how we understand, experience, and make home, yet tenure is often overlooked in literature that explores theories of home and homemaking. Secondly, the small amount of literature that does examine the experiences of renters focuses on how tenancy law could negatively impact or restrict renters within their homes. The cultures and practices of homemaking among renters are, for the most part, overlooked. Given the recent changes in housing trends, now, more than ever, it seems pertinent that we begin to understand some of the ways tenure might influence meanings of home and homemaking practices.